Legion Norge. Forskelle og ligheder med de øvrige »germanske« legioner i Waffen SS - Bundgård Christensen, Claus; Poulsen, Niels Bo; Scharff Smith, Peter (Historisk Tidsskrift, 2013)
The Norwegian Legion of the Waffen SS. A Comparison with other »Germanic« LegionsIn the course of World War II some six thousand Norwegians served as volunteers in the Nazi German military organisation Waffen SS. While most of them were assigned to divisions that included both Germans and volunteers from other countries, about 2,300 served under the Waffen SS in a separate national unit, the Legion Norge. The present study reviews the history of this unit on the basis of new sources, seeking specifically to answer three questions: the degree of its autonomy in relation to the SS, the enforcement of disciplinary rules, and troop morale. Comparisons are drawn with its Danish counterpart, Frikorps Danmark, and to a somewhat lesser extent with two other "Germanic" legions, the Flemish and the Dutch. While the SS subjected all the legions to a high degree of uniformity, there were nevertheless considerable differences in the way that policy interacted with internal conditions. Conflict between the legionnaires and the German Waffen SS were characteristic of the Norwegian as well as the Flemish and Dutch legions, while conflict in the Danish unit was to a larger extent between Nazi and non-Nazi members. The problem in the Danish legion was solved by the appointment of a charismatic leader. Moreover, troop morale was apparently better here than in the Norwegian legion, where it was worsened by the bad relations with the Germans and a lengthy standstill at the front. Translated by Michael Wolfe